Roles of STAT3 in the pathogenesis and treatment of glioblastoma - Fu, Weijia; Hou, Xue; Dong, Lihua; Hou, Wei (Frontiers in Cell and Developmental Biology, 2023)
Glioblastoma (GBM) is the most malignant of astrocytomas mainly involving the cerebral hemispheres and the cerebral cortex. It is one of the fatal and refractory solid tumors, with a 5-year survival rate of merely 5% among the adults. IL6/JAK/STAT3 is an important signaling pathway involved in the pathogenesis and progression of GBM. The expression of STAT3 in GBM tissues is substantially higher than that of normal brain cells. The abnormal activation of STAT3 renders the tumor microenvironment of GBM immunosuppression. Besides, blocking the STAT3 pathway can effectively inhibit the growth and metastasis of GBM. On this basis, inhibition of STAT3 may be a new therapeutic approach for GBM, and the combination of STAT3 targeted therapy and conventional therapies may improve the current status of GBM treatment. This review summarized the roles of STAT3 in the pathogenesis of GBM and the feasibility of STAT3 for GBM target therapy.